2017
DOI: 10.1016/j.parint.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Microcotyle (Monogenea: Microcotylidae) from Scorpaena notata (Teleostei: Scorpaenidae) in the Mediterranean Sea

Abstract: We collected specimens of Microcotyle spp. from two species of scorpaeniform fishes off Algeria, namely Scorpaena notata and Helicolenus dactylopterus. The identification of both fishes was confirmed by molecular barcoding of the COI gene. Sequences of COI gene were also obtained for both parasite species. The species from S. notata is described as Microcotyle algeriensis n. sp., on the basis of morphological differences from other species (number of clamps, number of spines in genital atrium, number of testes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(73 citation statements)
references
References 23 publications
3
70
0
Order By: Relevance
“…Recent studies have shown that the biodiversity of monogeneans of marine fish in the southern part of the Mediterranean is far from being completely known (Chaabane et al, 2015(Chaabane et al, , 2016a(Chaabane et al, , b, 2017Chaari et al, 2016;Kheddam et al, 2016;Boudaya & Neifar, 2016;Ayadi et al, 2017). In the course of a parasitological study of monogeneans of sparid fishes off the Algerian coast, we collected representatives of an undescribed species of Microcotyle on the gills of Pagrus caeruleostictus.…”
Section: Microcotyle Visamentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that the biodiversity of monogeneans of marine fish in the southern part of the Mediterranean is far from being completely known (Chaabane et al, 2015(Chaabane et al, , 2016a(Chaabane et al, , b, 2017Chaari et al, 2016;Kheddam et al, 2016;Boudaya & Neifar, 2016;Ayadi et al, 2017). In the course of a parasitological study of monogeneans of sparid fishes off the Algerian coast, we collected representatives of an undescribed species of Microcotyle on the gills of Pagrus caeruleostictus.…”
Section: Microcotyle Visamentioning
confidence: 99%
“…During the 21st century, new genera (Omanicotyle Yoon, Al-Jufaili, Freeman, Bron, Paladini & Shinn, 2013, Paranaella Kohn, Baptista-Farias & Cohen, 2000 (see Kohn et al, 2000;Yoon et al, 2013) and species [Microcotyle algeriensis Ayadi, Gey, Justine & Tazerouti, 2017, M. argenticus Hadi & Bilqees, 2011, M. rubrum Hadi & Bilqees, M. jonii Hadi, Bilqees & Khatoon, 2011, M. omanae Machkewskyi, Dmitrieva, Al-Jufaili & Al-Mazrooei, 2013 and Polylabris bengalensis Sailaja & Madhavi, 2011] have been added to this family (Hadi & Bilqees 2010, 2011Sailaja & Madhavi, 2011;Machkewskyi et al, 2013;Ayadi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements are in micrometers, and indicated as means ± standard deviation (if n > 30), and between parentheses the range and number (n) of structures measured. Because measured lengths may vary depending on how specimens are prepared and the degree to which they are flattened [2,21], they are given separately for specimens mounted respectively in Malmberg's medium (m) or stained in carmine and mounted in Canada balsam (c).…”
Section: Morphological Analysismentioning
confidence: 99%
“…In the present study, integrative taxonomy based on molecular and morphological analyses was used to provide a formal description of a new species and the proposal of a new genus for its accommodation. This paper belongs to a series of papers dealing with the morphological and molecular description of monogeneans from off the southern Mediterranean coast [2][3][4][5][6][7]22].…”
Section: Introductionmentioning
confidence: 99%